Safety and Efficacy of Programmed Cell Death 1 and Programmed Death Ligand-1 Inhibitors in the Treatment of Cancer: An Overview of Systematic Reviews - Ou, Shun-Long; Luo, Jing; Wei, Hua; Qin, Xiao-Li; Du, Su-Ya; Wang, Song; Jiang, Qian (Frontiers in Immunology, 2022)
Background An influx of systematic reviews (SRs) of programmed cell death 1 (PD-1) and programmed death ligand-1 (PD-L1) checkpoint inhibitors in cancer treatment with or without meta-analysis and with different methodological quality and inconsistent results have been published, confusing clinical decision making. The aim of this study was to comprehensively evaluate and summarize the current evidence of PD-(L)1 inhibitors in the treatment of cancer. Methods A comprehensive search of SRs, which included meta-analyses of PD-(L)1 inhibitors on cancer, was performed on eight databases with a cutoff date of 1 January 2022. Two authors independently identified SRs, extracted data, assessed the report quality according to the guidance of the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement, evaluated the methodological quality by the Assessment of Multiple Systematic Reviews 2 (AMSTAR 2), and appraised the quality of evidence by the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE). Results A total of 172 SRs with meta-analysis met the inclusion criteria. The report quality of included SRs was quite good, with 128 (74.42%) SRs of high quality and 44 (25.58%) of moderate quality. The methodological quality was alarming, as only one (0.58%) SR had high quality, five (2.91%) SRs had low quality, and the other 166 (96.51%) SRs had critically low quality. For GRADE, 38 (3.77%) outcomes had high-quality evidence, 288 (28.57%) moderate, 545 (54.07%) low, and 137 (13.59%) critically low-quality evidence. Current evidence indicated that treatment with PD-(L)1 inhibitors were significantly effective in non-small cell lung cancer, small cell lung cancer, hepatocellular carcinoma, malignant melanoma, renal cell carcinoma, and urothelial carcinoma, breast cancer, and head and neck squamous cell carcinoma with PD-L1 expression level≥1%, whereas the evidence in gastroesophageal and colorectal tumors is still controversial. Monotherapy with PD-(L)1 inhibitors was associated with a lower frequency of any grade and high-grade adverse events (AEs). The incidence of any grade and high-grade AEs caused by PD-(L)1 inhibitors in combination with other therapies was no lower than the controls. However, PD-(L)1 inhibitors were associated with a higher frequency of any grade and high-grade immune-related AEs. Conclusions PD-(L)1 inhibitors appeared to be effective and safe for cancer treatment, except for gastrointestinal tumors; however, the quality of the evidence is not convincing. Future studies should improve methodological quality and focus on the sequential trial analysis of subgroups and safety. Systematic Review Registration http://www.crd.york.ac.uk/prospero, identifier CRD42020194260.